Xist and the order of silencing - Ng, Karen (2007)
X inactivation is the mechanism by which mammals adjust the genetic imbalance that arises from the different numbers of gene-rich X-chromosomes between the sexes. The dosage difference between XX females and XY males is functionally equalized by silencing one of the two X chromosomes in females. This dosage-compensation mechanism seems to have arisen concurrently with early mammalian evolution and is based on the long functional Xist RNA, which is unique to placental mammals. It is likely that previously existing mechanisms for other cellular functions have been recruited and adapted for the evolution of X inactivation. Here, we critically review our understanding of dosage compensation in placental mammals and place these findings in the context of other cellular processes that intersect with mammalian dosage compensation.